2012
DOI: 10.1016/j.jvs.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Difference in Systolic Blood Pressure Between Arms with Vascular Disease and Mortality: A Systematic Review and Meta-analysis

Abstract: Conclusion:Antioxidant consumption can acutely restore endothelial dysfunction in elderly patients.Summary: Endothelial dysfunction likely contributes to atherosclerosis through a reduction in bioavailability of nitrite oxide (NO). There is also an age-related increase in plasma free radical concentration that contributes to a decrease in the bioavailability of NO. The authors investigated whether acute antioxidant treatment would result in a reversal of the decrease in endothelial function in elderly patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
194
4
25

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(235 citation statements)
references
References 0 publications
12
194
4
25
Order By: Relevance
“…1 On recent meta-analysis the authors observed a trend towards higher HRs for survival differences when using simultaneous IAD measurement methods compared with sequential methods, thus survival differences reported here may under-estimate the true figures for this cohort. 25 This analysis was undertaken following publication of the AAA trial and was not specifically powered to assess a pre-defined difference in survival by IAD.…”
Section: Strengths and Limitationsmentioning
confidence: 67%
See 4 more Smart Citations
“…1 On recent meta-analysis the authors observed a trend towards higher HRs for survival differences when using simultaneous IAD measurement methods compared with sequential methods, thus survival differences reported here may under-estimate the true figures for this cohort. 25 This analysis was undertaken following publication of the AAA trial and was not specifically powered to assess a pre-defined difference in survival by IAD.…”
Section: Strengths and Limitationsmentioning
confidence: 67%
“…47 Some authors have labelled an IAD ≥15 mmHg 'subclavian stenosis', 7,48 but there is no direct radiological evidence from general populations, such as the cohort studied here, to confirm that this is the anatomical cause of an IAD. 1 Structural changes in large arteries as a result of hypertension begin early in the course of the condition and cardiovascular and peripheral vascular disease are late sequelae of a process of gradual arterial stiffening. 49 Recent cross-sectional studies have associated systolic IADs ≥10 mmHg with elevated ankle-brachial pulse wave velocity, an indicator of increasing vascular stiffness.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 3 more Smart Citations